The Effectiveness of Supervisory Performance on the Implementation Sustainability Development Goals & The Green Economy - Irfan; Bonnix Hedy Maulana (International Economic Conference of Business and Accounting, 2024)
This study aims to analyze the effectiveness of supervision performance by the Kudus Inspectorate on improving public services, with an emphasis on the implementation of the Sustainable Development Goals (SDG's) and the concept of green economy. The research method used is qualitative descriptive, the research informants consist of Kudus Inspectorate officials, internal auditors, and employees. The results show that the monitoring carried out not only ensures compliance with regulations, but also promotes SDG's principles; peace, justice and strong institutions (SDG 16) and partnerships for the goals (SDG 17). In addition, the application of the green economy concept can be seen in supervisory efforts that encourage resource efficiency and environmentally friendly practices in the provision of public services. However, this study also found several challenges faced by the Kudus Inspectorate, such as limited human resources and technology, as well as resistance from OPDs in adopting new practices. Keywords: Green Transactions; Local Government; Supervisory Performance; Sustainable Development Goals (SDG's),